Hubungan Suhu Rumah dengan Kejadin Hipertensi - Muhammad Halil Gibran; Farida Heriyani; Djallalluddin Djallalluddin (Homeostasis, 2020)
Abstract: High population density and dense housing in the area of Banjarmasin East Kelayan Health Center can trigger a hot temperature in the region. As a result of these hot temperatures can increase levels of stress hormones, such as epineprin, non-epineprin and cortisol, the body can cause hypertension. The purpose of this study is to determine the relationship of home temperature with the incidence of hypertension in dense residential dwellings in the area of Health Center East Kelayan Banjarmasin. This study uses an analytic observational method with a case control approach. The sample of this study was hypertension and non-hypertension patients based on medical record data which was according to the diagnosis by the doctor at the Kelayan East Health Center in Banjarmasin. The method of sampling uses random sampling technique which is divided into 30 groups of hypertensive cases and 30 control groups without hypertension and obtained as many as 60 samples that fit the inclusion criteria. Data analysis using Chi square test. The results of this study in the case group there were 76.7% of patients with hypertension at high temperatures, 23.3 low temperatures while the control group contained 40% of patients without hypertension at high temperature, 60%. The results of the analysis were obtained (p = 0.009 OR = 4,929) there is a significant relationship between house temperature and the incidence of fist hypertension in dense residential dwellings in the Banjarmasin Kelayan Timur Health Center area. Keywords: House Temperature, Solid residence, Hypertension. Abstrak: Kepadatan penduduk yang tinggi dan hunian rumah yang padat di wilayah Puskesmas Kelayan Timur Banjarmasin dapat memicu suatu suhu panas di wilayah tersebut. Akibat dari suhu panas tersebut dapat meningkatkan pelebaran vasodilatasi pembuluh darah tepi dan vasokontraksi pembuluh darah dalam yang disertai terjadi peningkatan denyut nadi dan tekanan darah naik menyebabkan hipertensi.Tujuan penelitian ini adalah mengetahui hubungan suhu rumah dengan kejadian hipertensi pada hunian rumah yang padat di wilayah Puskesmas Kelayan Timur Banjarmasin. Penelitian ini dengan menggunakan metode observasionaal analitik dengan pendekatan case control. Sampel penelitian ini pasien hipertensi dan tidak hipertensi berdasarkan data rekam medis yang sesuai diagnosis dokter Puskesmas Kelayan Timur Banjarmasin. Pengambilan sampel dengan menggunakan teknik random sampling. Analisis data menggunakan uji Chi square. Hasil penelitian ini pada kelompok kasus terdapat 76,7% penderita hipertensi berada tinggal di rumah suhu yang tinggi, 23,3% suhu rendah sedangkan kelompok kontrol terdapat 40% penderita tidak hipertensi berada tinggal di rumah suhu yang tinggi, 60% suhu rendah. Hasil analisis diperoleh (p=0,009 OR=4,929) terdapat hubungan signifikan antara suhu rumah dengan kejadian hipertensi tinjuan pada hunian rumah yang padat di wilayah‘Puskesmas Kelayan Timur Banjarmasin. Kata-kata kunci: Suhu rumah, Hunian padat, Hipertensi